The Role Of Jalan Rukunan In The Kampung Of Kotagede Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Biologi UGM, 2000)
The paper is aimed to identify the role of what so called "Jalan Rukunan" in. Kotagede and its physical characteristics, as well as its interconnection and growth during a certain period of time, through a qualitative approach. Certain numbers of samples are selected purposively and sampling ends when repetition occurred. The unit of analysis is Jalan Rukunan and its surroundings, both in terms of physical environment and activities conducted within the neighborhood. The research divided the period into three categories: (1) between 1930-1950, (2) between 1950-1970, and (3) between 1970-1990.